ELECTRICAL CONDUCTIVITY OF CORDIERITE - Schmidbauer E.; Mirwald P.W. (My University, 1993)
Electrical ac-conductivity parameters (real part of impedance (Z′), imaginary part of impedance (-Z″) and parallel capacity (Cp)) of a low iron cordierite single crystal from White Well, Australia (Mg1.91 Fe0.08 Mn0.01Al3.95 Si5.01 (Na0.05, 0.56 H2O, mCO2)) (Pryce, 1973) were studied in the temperature range 200 to 820°C and frequency range 25 – 106 Hz with a test signal voltage of 1.0 volt. Measurements on the 4.2 x 3.4 x 4.7 mm sample were conducted in the crystallographic [001]- and [100] -directions in order to elucidate the electrical behaviour of this orthorhombic framework silicate parallel and normal to its c-parallel channel elements which host a variety of alkali and fluid components. The first heating excursion up to 900°C took ca. 8 hours to allow a slow degassing of the fluid components. The electrical parameters were monitored during this irreversible process. The subsequent measurement cycles did not exceed 820°C and yielded reproducible data. The data obtained in the two different crystallographic directions indicate a considerable anisotropy in electrical behaviour. While plots of the Z′- vs. -Z″-data obtained in the [001]-direction show two semicircular arcs, those in the [100] -direction display only one such arc. Each of the arcs may be related to a charge transfer process in the crystal. Estimates of the activation energies of the different inferred charge transfer processes derived from a plot of extrapolated RDC vs. 1/T are 0.75 and 0.83 eV for the [001]- and 0.85 eV for the [100] -direction. The occurrence of different charge transfer processes combined with large differences in the values of the Z′- and - Z″-parameters indicate a considerable anisotropic electrical behaviour of cordierite which can clearly be related to its structural characteristics. Further work is needed to elucidate the electrical conduction mechanisms.